Cauda equina paragangliomas express HOXB13. (5th April 2021) - Bockmayr, Michael; Körner, Meik; Schweizer, Leonille; Schüller, Ulrich
Abstract : HOXB13 is expressed in the tail bud of the developing embryo as well as in cauda equina paragangliomas and in myxopapillary ependymomas. In contrast, pheochromocytomas and paraganglioma in other locations as well as many other tumors occuring in spinal cord regions are negative.